Pulmonary blastoma. Rare clinical case. - Shevchenko, A. I.; Likhachov, S. S.; Shatovskiy, Yu. O. (Zaporozhye Medical Journal, 2013)
The case of diagnosis of asymptomatic lung blastoma in 61years old man was described.